MARKET CONCENTRATION AND DEMAND FOR ALCOHOLIC BEVERAGES IN MAJOR MOTOR PARKS WITHIN IBADAN METROPOLIS, OYO STATE, NIGERIA - Sowunmi, Fatai; AKINMULEYA , Ayobami Stephen AKINMULEYA (Applied Studies in Agribusiness and Commerce, 2023)
The value addition to alcoholic beverages through packaging in small nylon and increase in the introduction of new brands has led to its high demand and many Nigerians earning their means of livelihood through the sales. The study showed that the average consumption per day was 6.1 sachets per week. The study revealed that 28.6% of the consumers’ monthly income was spent on alcoholic beverages per month. Seaman brand had the highest market share (73.4%); this was followed by Chelsea (66.2%). The study affirmed that 62.9% of the consumers based their choice on high alcoholic content while 3.1% claimed the choice was based on the medicinal (cures pile) value. Also, Captain Jack had the highest market concentration (0.35). The age of respondents, marital status, household size, and the quantity consumed per week were the factors that influenced consumers’ monthly expenditure on alcoholic beverages. It is recommended that efforts should be made by the government to reduce the rate of consumption of alcoholic beverages at the motor parks by enforcing the existing (FRSC Act cap 141 Laws of the Federation of Nigeria) law banning/regulating the sales or increasing tax on the brands to make it out of reach for most consumers.